Analisis Perbandingan Prediksi Kebangkrutan Perbankan Syariah dan Konvensional di Indonesia - Muhammad Ichsan Adnan; Heru Fahlevi (Universitas Andalas, 2020)
The purpose of this study was to compare the stability of Islamic and conventional banking in Indonesia by measuring financial distress/ bankruptcy predictions through the Altman Z-Score and Grover G-Score methods for a period from 2016 to 2018. The study evaluated 11 Islamic banks and 40 conventional banks by using Independent Sample T-Test. The results in this study indicated a difference between Islamic and conventional banking based on the Altman Z-Score and Grover G-Score methods. Calculations based on the Altman Z-Score method on Islamic banks indicated that there were 2 banks that were not bankrupt, 1 bankrupt and 11 banks were in the grey zone. Whereas in conventional banks there were 2 banks that were predicted not to go bankrupt, 25 banks that were in the grey area, and 13 banks were predicted to go bankrupt. Based on the Grover G-Score calculation, there were no bankrupt banks, both Islamic banks and conventional banks. The study showed that Islamic banks were more stable than conventional banks.